2016
DOI: 10.1682/jrrd.2015.04.0061
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of extremely low-frequency magnetic field in fibromyalgia pain: A pilot study

Abstract: Abstract-The purpose of this pilot study was to determine the efficacy of an extremely low-frequency magnetic field (ELF-MF) in decreasing chronic pain in fibromyalgia (FM) patients. Thirty-seven females were recruited and randomized into two groups: one group was first exposed to systemic ELF-MF therapy (100 microtesla, 1 to 80 Hz) and then to sham therapy, and the other group received the opposite sequence of intervention. Pain, FM-related symptoms, and the ability to perform daily tasks were measured using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 45 publications
(53 reference statements)
0
19
2
Order By: Relevance
“…Our finding is contrary to that of a previous RCT by Sutbeyaz et al [] and a pilot study by Paolucci et al [], showing that both PEMF and a nonpulsed magnetic field delivered by whole‐body mats had beneficial effects on fibromyalgia patients’ disease impact and pain intensity after somewhat short treatment periods. Instead, our finding is in line with another RCT by Alfano et al [], who found no improvement from static magnetic sleep pads on functional status measured by FIQ, although active magnetic sleep pads decreased pain intensity significantly more than inactive pads did in the control group.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our finding is contrary to that of a previous RCT by Sutbeyaz et al [] and a pilot study by Paolucci et al [], showing that both PEMF and a nonpulsed magnetic field delivered by whole‐body mats had beneficial effects on fibromyalgia patients’ disease impact and pain intensity after somewhat short treatment periods. Instead, our finding is in line with another RCT by Alfano et al [], who found no improvement from static magnetic sleep pads on functional status measured by FIQ, although active magnetic sleep pads decreased pain intensity significantly more than inactive pads did in the control group.…”
Section: Discussioncontrasting
confidence: 99%
“…Instead, our finding is in line with another RCT by Alfano et al [2001], who found no improvement from static magnetic sleep pads on functional status measured by FIQ, although active magnetic sleep pads decreased pain intensity significantly more than inactive pads did in the control group. However, the electromagnetic signals, dosage of the treatments, and study durations (three weeks in Sutbeyaz et al [2009]; 4 weeks in Paolucci et al [2016]; and 6 months in Alfano et al [2001]) were different than those in the present study. In addition, the results of the above-mentioned previous studies should be interpreted with caution due to the small sample sizes in each treatment arm, which increases the possibility that positive results are due to chance.…”
Section: Discussioncontrasting
confidence: 77%
“…Fibromyalgia has demonstrated some significant short-term pain relief with PEMF but it is also plagued by inconsistencies. For instance, Sutbeyza et al [59] and Paolucci et al [60] reported studies which demonstrated that both PEMF and "nonpulsed magnetic field delivered by whole-body mats" had significant beneficial impacts on fibromyalgia patients in relation to disease impact and pain intensity. In addition, a randomized, double-blind study done in 2009 by Multanen et al [54] and another done by Alfano et al [61] found no improvement in fibromyalgia patients treated with PEMF.…”
Section: Candidacymentioning
confidence: 99%
“…[14][15][16] Furthermore, the efficacy of magnetotherapy compared to some forms of chronic pain such as fibromyalgia (FM) still remains debated. 17,18 Moreover, also in neurological pathology, ELF magnetic field was revealed to induce a significant improvement in functional and mental status in brain stroke patients and clinical parameters had positive correlation with the level of enzymatic antioxidant protection. 7 Thus, surely, the efficacy of magneto-therapy is related to the type of electromagnetic fields used and in the rehabilitation field there are today very different treatment protocols: certainly, in the last decade, the use of ELF magnetic fields has been on its increase.…”
Section: Introductionmentioning
confidence: 98%